Policymakers' Online Use of Academic Research - Willinsky, John (Education Policy Analysis Archives, 2003)
In addressing the question of how new technologies can improve the public quality and presence of academic research, this article reports on the current online use of research by policymakers. Interviews with a sample of 25 Canadian policymakers at the federal level were conducted, looking at the specific role that online research has begun to play in their work, and what frustrations they face in using this research. The study found widespread use of online research, increasing the consultation of this source in policy analysis and formation. The principal issues remain those of access, indexing and credibility, with policymakers restricting themselves in large part to open access sources. Still, online research is proving a counterforce to policymakers' reliance on a small number of academic consultants as gatekeepers and sources for research. What is needed, it becomes clear, is investigations into whether innovative well-indexed systems that integrate a range of academic and non-academic resources might increase the political impact of research in the social sciences and education.